Knowledge management for process, organizational and marketing innovation : tools and methods - O'Brien, Emma; Clifford, Seamus; Southern, Mark, 1967- (Premier reference source, 2011)
"This book outlines different tools and technologies that can be applied depending on the type of innovation an organization desires, providing concrete advice on the different types of innovation, situations in which innovation may be useful and the role of knowledge and different tools and technologies to support it"--Vydavatelská anotace